Approach to Loss of Consciousness: Distinguishing Epileptic Seizures, Psychogenic Nonepileptic Seizures, and Syncope - Ebong, Ima; Haghighat, Zahra; Bensalem-Owen, Meriem (Seminars in Neurology, 2021)
Transient loss of consciousness (TLOC) is a common emergent neurological issue, which can be attributed to syncope, epileptic seizures, and psychogenic nonepileptic seizures. The purpose of this article is to outline an approach to diagnosing the most common etiologies of TLOC by focusing on the importance of the history and physical examination, as well as targeted diagnostic tests.
Keywords: transient loss of consciousness; loss of consciousness; seizures; syncope; psychogenic nonepileptic seizures